Recent ornithological observations from Buru - Jepson, Paul (KUKILA, 1992)
The island of Buru was visited between 8 Nov and 10 Dec 1969 and surveys conducted from field stations in the north-west of the island. A total of 112 species was recorded, including six of Bum's ten endemic species. Four of the endemic species, Pnoniturus mada, Monarcha loricatus, Rhipidura superflua and Zosterops buruensis were found to be quite common, but Lichmera deningeri and Coracina fortis are considered to be uncommon or rare. The mountains or Burn from where Madanga ruficollis and Rhinomyias addita have previously been collected were not visited. Concern is expressed concerning the status of two endemic parrots, Charmosyna toxopei and Tanypiathus gramineus, which were not conclusively recorded and which appear to have always been rare. Six species were recorded for the first tune on Buru.